The Bad Guys in Attack of the zittens - Blabey, Aaron (New York, NY Scholastic Inc, 2017)
"It's a zombie kitten apocalypse! Can the Bad Guys save the world from evil Dr. Marmalade's meowing monsters?!? They'll need help from foxy Agent Fox, a swampy secret zombie antidote, and the feistiest, toothiest, hungriest granny around. Get ready to watch the fur fly!"--Page 4 of cover
English stories
"First published by Scholastic Australia Pty Limited in 2016."
Keywords: Animals -- Juvenile fiction; Zombies -- Juvenile fiction; Rescues -- Juvenile fiction; Kittens -- Juvenile fiction; Cats -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous stories; Illustrated children's books; Graphic novels; Animals -- Fiction; Zombies -- Fiction; Rescues -- Fiction; Cats -- Fiction; Heroes -- Fiction; Humorous stories -- Fiction; Illustrated children's books -- Fiction; Humorous stories; Graphic novels; Humorous stories; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Animals; JUVENILE FICTION -- Humorous Stories; Graphic novels; Animals; Zombies; Rescues; Kittens; Cats; Heroes; Humorous stories; Illustrated children's books; Animals -- Fiction; Humorous fiction; Heroes -- Fiction; Graphic novels; Humorous fiction; Graphic novels; Fiction; Juvenile works; Humorous fiction